Functional impacts of lactylation in Hypoxia‒primed mesenchymal stromal cells - Zhao, Fanyi; Tang, Qixing; Liu, Jie (Frontiers in Cell and Developmental Biology, 2025)
Hypoxic culture (1–5% O2) significantly enhances the biological activity and therapeutic potential of mesenchymal stromal cells (MSCs) by activating the HIF-1α signaling pathway. This activation promotes stemness maintenance, enhances proliferative capacity, and improves immunomodulatory functions, such as upregulating the secretion of indoleamine 2,3‒dioxygenase (IDO) and prostaglandin E2 (PGE2). Furthermore, hypoxia optimizes paracrine effects through modulating the release of vascular endothelial growth factor (VEGF) and hepatocyte growth factor (HGF), while also improving cell homing and post-transplantation survival rates. Under hypoxic conditions, MSCs primarily rely on glycolytic metabolism, resulting in lactate accumulation. This lactate serves not only as a metabolic byproduct but also as a precursor for lactylation, a novel form of epigenetic modification. Given the limited research on MSC-specific metabolic mechanisms driven by lactylation, investigating lactylation modifications‒such as histone H3 lysine 18 lactylation (H3K18la)‒and their impact on MSCs function is crucial. We propose that the ‘hypoxia-lactate-lactylation’ axis represents a key metabolic-epigenetic mechanism that may further enhance immunomodulatory and tissue‒repair capabilities via epigenetic regulation, offering novel targets for metabolic intervention in clinical cell therapy. This approach could maximize the therapeutic potential of MSCs in clinical applications, with a high safety profile that avoids risks such as tumorigenicity, donor-dependent variability, and senescence.